Uma jornada aos anéis de Gorenstein - Dosea, André Santana (2019)
This work has as main goal to make a detailed study of Gorenstein rings and your role in local duality theory. At the beginning, some pre-requisites are studied like the Krull dimension of modules, Koszul Complexes and Cohen-Macaulay rings. Concerning to this last topic, we studied in more detail the regular rings and the complete intersection rings. We showed that all this rings are Gorenstein. Also, we present the characterization of Gorenstein rings in terms of the concept of type of a ring. Ultimately, we present the concept of canonical module, highlighting your role in Local Duality Theory over maximal Cohen-Macaulay modules.